ANALYSIS OF EDUCATION AND SERVICES ON TAX PAYMENT DECISIONS WITH SOCIAL MEDIA AS AN INTERVENING VARIABLE AT THE LUBUK PAKAM TAX OFFICE - Fitri Heldaliani; Nurafrina Siregar; Erwansyah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study analyzes the effect of tax education and fiscal service quality on tax payment decisions, with social media as an intervening variable, among individual taxpayers in the Lubuk Pakam Tax Office jurisdiction. The background of this research stems from the low score for the statement "paying on time" and inconsistent positive interaction experiences, despite the expansion of digital transformation (e.g., Coretax) and online communication channels. The method used is a quantitative approach with an associative design; a sample of 100 taxpayers (treasurers) was selected using the Slovin formula. Data collection was conducted from July to October 2025 through a Likert questionnaire and analyzed using PLS-SEM (SmartPLS). The results show a significant direct influence: education → decision to pay (β=0.221; p=0.041), service → decision to pay (β=0.214; p=0.018), education → social media (β=0.594; p<0.001), service → social media (β=0.330; p=0.012), and social media → decision to pay (β=0.520; p<0.001). Indirect effects were also significant: education → social media → payment decision (β=0.309; p=0.003) and service → social media → payment decision (β=0.172; p=0.026). The model had high explanatory power (R² social media=0.813; R² payment decision=0.845), confirming the mediating role of social media. Practical implications for the Tax Office: (i) microlearning programs & short content on social media, (ii) responsive omnichannel (chatbot/DM/live chat) that closes with specific calls to action (create a Billing ID, add reminders), and (iii) strengthening the habit of paying H-3 through the "10-25-28" campaign and One-Stop Billing ID at the counter. These findings confirm that improved education and services supported by effective social media can encourage timely tax payment decisions.